A Comparative Analysis of Inhibitory Effect of Different Levels of Ya'an Tibetan Tea on Lipase. (June 2020) - Xu, Jingyi; Wang, Weiyi; Du, Mengze; He, Chunlei; Bian, Jinlin; Du, Xiao
Abstract: In this experiment, the inhibition effects in vitro and inhibition type of different levels of Ya'an Tibetan tea on lipase were studied by measuring its biochemical components, enzyme activity, and semi-inhibitory concentration. The results showed that the higher the grade of Ya'an Tibetan tea, the higher the content of water extracts, tea polyphenols, caffeine, free amino acids, soluble sugars and theabrownins. At the same tea soup concentration, the inhibition rate of all of Ya'an Tibetan tea on lipase showed an increasing trend with the increase of tea soup concentration. The IC50 of the semi-inhibitory concentration of inhibitory effect of each tea sample on lipase was greater than 20 mg. mL −1 . The order of the inhibitory ability on lipase were Jixiang level one and Jixiang level three>Jixiang level two, Yixing level one and Yixing level three>Yixing level two. The inhibition types were all mixed type of reversible inhibition between competitive and non-competitive inhibition, which was closer to competitive inhibition. The inhibition was a mixed type of reversible competitive and non-competitive inhibition, which was close to the competitive inhibition. The results showed that different levels of Ya'an Tibetan tea had good inhibitory effects on lipase, and could be developed and used as natural lipase inhibitors.